Effect of MgCl Treatment and High pH on the Removal of Phosphate Content in Palm Oil Mill Effluent - Galang Indra jaya Jaya (Jurnal Biologi Tropis, 2023)
The development trend of oil palm plantations and mills in Indonesia is very rapid. The processing of fresh fruit bunches (FFB) into crude palm oil (CPO) produces the by-product palm oil mill effluent (POME). This by-product contains very high levels of phosphate (P), BOD & COD. These elements will become contaminants and the environment. The research conducted aimed to test the best MgCl dose that can remove P in POME and determine the effect of the treatment given on BOD & COD values. The research was conducted using the struvite making method approach, the treatments tested were MgCl doses of 50 & 100 grams of MgCl per 500 ml of POME that had been maintained at pH 9 with 1N KOH solution. The results showed that the 50 gram MgCl treatment was better at removing P in the solution reaching 80% while the 100 gram MgCl treatment had a removal value of < 2%. BOD & COD values before and after treatment showed no difference, observation with SEM showed that the crystals were not formed completely which supported the very low P & N value of < 1%. The best P removal from POME was in the 50 g MgCl treatment, but the P & N content in the sediment in all treatments was still very low, and all treatments did not change the BOD & COD values, so for development, integrated waste management is needed to change the nature of the waste to meet environmental quality standards.